The value of three-dimensional photogrammetry in isolated sagittal synostosis: Impact of age and surgical technique on intracranial volume and cephalic index$da retrospective cohort study - Mertens, Christian; Wessel, Eline; Berger, Moritz; Ristow, Oliver; Hoffmann, Jürgen; Kansy, Julia Katharina; Freudlsperger, Christian; Bächli, Heidi; Engel, Michael (Journal of cranio-maxillofacial surgery, 2017)
Purpose: The aim of this study was to compare the outcome of intracranial volume (ICV) and cephalic index (CI) between two different techniques for surgical therapy of sagittal synostosis. Material and methods: Between 2011 and 2015, all patients scheduled for surgical therapy of sagittal synostosis were consecutively enrolled. All patients younger than 6 months underwent early extended strip craniectomy (ESC group), and patients older than 6 months underwent late modified pi-procedure (MPP group). To measure ICV and CI, data acquisition was performed via three-dimensional photogrammetry, 1 day before (T0) and between 10 and 12 weeks after surgery (T1). Results were compared with an age-matched reference group of healthy children. Perioperative parameters, as duration of surgery and the amount of blood loss of both surgical procedures were analyzed. Results: A total of 85 patients were enrolled. Of the patients, 48 underwent an extended strip craniotomy with parietal osteotomies and biparietal widening and 37 patients underwent a late modified pi-procedure. There was no significant difference between the ESC group and the MPP group regarding the efficacy of improving CI (p > 0.05). Both techniques were able to normalize CI and to improve head shape. ICV was normal compared to age-matched norm-groups with both techniques, pre- and postoperatively. However, duration of the surgical procedure and calculated blood loss were significantly lower in the ESC group (p < 0.05). Conclusion: ESC and MPP were effective techniques to normalize cephalic index (CI) and improve head shape at their recommended time of surgery. Measurement of ICV and CI with 3D photogrammetry is a valid method to objectively evaluate patients before and after surgery without exposing pediatric patients to ionizing radiation.